Implementation of drug substitution therapy in Georgia - Todadze, Khatuna; Lezhava, Gela (Central European journal of public health, 2008)
The geopolitical uniqueness of the regional, socioeconomic situation and the existence of territories outside the control of the national government have facilitated the spread of drug use in Georgia. A special problem is injection of opiates, in particular heroin and Subutex (buprenorphine). It has been established that among registered HIV infected individuals the main route of transmission is injecting drug use. Although the prevalence of HIV among IDUs (injecting drug user) is only 1-3%, the high number of IDUs, and the high prevalence of hepatitis C in this population creates high risk of dramatic spread of HIV in Georgia. Beginning at the end of 2005, the GFATM (Global Fund against HIV/AIDS, Tuberculosis and Malaria) supported methadone substitution programmes in Georgia. At present, three programmes are functioning. At the same time, they involve 230 patients altogether. The studies carried out by the Research Institute on Addiction, with the aim to control the efficacy of pilot programmes have revealed a dramatic improvement of psychophysical state of patients, with very high rate of resocialization and decriminalization, significant diminishment of drug-related risky behaviour. Obtained results indicate high efficiency of methadone substitution programmes in Georgia, as an important tool both for treatment of opioid dependence and harm reduction. In order to obtain a more significant impact on public health substitution therapy programmes have to be further expanded.
Keywords: poruchy spojené s užíváním psychoaktivních látek; methadon; snížení rizika poškození; Georgia (Republic); Methadone; Substance Abuse, Intravenous; Humans; Gruzie; hepatitida C; intravenózní abúzus drog; Narcotics; lidé; Psychology; psychologie; HIV infekce; narkotika; Treatment Outcome; Harm Reduction; HIV Infections; Hepatitis C; Substance-Related Disorders; výsledek terapie